A review of robotics application in manufacturing industry - Saadon, Zaid Kh.; Salim, Ghassan Maan; Omotoso, O. A.; Abdul Aziz, Faieza (Science and Knowledge Research Society, 2015)
Robots have different applications in many fields especially in manufacturing industry. Robots can be considered an important part of manufacturing industries due to the valuable advantages and different applications they offer. However, they also have negative impacts on workers who might be replaced with robots to their jobs, so these workers will be jobless. This paper is discussing the advantages of robots in manufacturing industry and how using robots is important in developing countries. Also some real studies are illustrated in figures showing the robot applications in different countries which are Korea, Japan and Taiwan.